The Socioeconomic Effect of COVID-19 Pandemic on Iranian Children: The Mediating Role of Parents' Mental Health - Majid Golzarpour; Homeira Sajjadi; Paula Santana; Gholamreza Ghaedamini Harouni; Claudia Costa; Arash Ziapour; Seyed Amar Azizi; Sima Afrashteh (Shiraz University of Medical Sciences, 2024)
Background: COVID-19 has been troublesome for families due to its socio-economic changes worldwide. Therefore, the present study aimed to investigate the socio-economic burden of COVID-19 on children's health in Iran.Methods: In the present cross-sectional study, the target population was 500 parents of children aged 5 to 18 years from 5 provinces of Iran in 2021. The samples were randomly selected from different geographical regions of Iran. The questionnaires on the socioeconomic burden of COVID-19, general health, child health, and place of residence landscape were employed to collect the data. For data analysis, t-test, structural equation modeling (SEM) were used in SPSS version 26 and AMOS version 26, respectively.Results: The results indicated that based on determination coefficients of socio-economic burden of COVID-19, the socioeconomic status of the parents and the settlement external perspective variable account for nearly 25% of the mental changes in parents. Furthermore, the combined effects of COVID-19's socioeconomic burden and parents' mental health accounted for 26% of the health changes observed in children. The socio-economic burden had a negative correlation with parents' mental health (β=-0.383, P<0.001) and children's health (β=-0.202, P=0.003). Nevertheless, a positive association was found between socioeconomic status and parents' mental health (β=0.138, P=0.014) on the one hand and the external settlement perspective with parents' mental health (β=0.243, P<0.001), on the other hand. Also, the parents' mental health showed a positive correlation with children's health (β=0.398, P<0.001).Conclusions: The present findings revealed that the socio-economic status and mental health of parents are important determinants of children's health; thus, health policymakers should prevent social economic inequalities during epidemics. Also, they should provide optimal support to vulnerable families to avoid negative effects on children's health.